'Wasn't offered one, too poorly to ask for one' – Reasons why some patients do not receive a psychosocial assessment following self-harm: Qualitative patient and carer survey. (April 2022) - Quinlivan, Leah; Gorman, Louise; Littlewood, Donna L; Monaghan, Elizabeth; Barlow, Stephen J; Campbell, Stephen; Webb, Roger T; Kapur, Nav
Objective: Psychosocial assessment following self-harm presentations to hospital is an important aspect of care. However, many people attending hospital following self-harm do not receive an assessment. We sought to explore reasons why some patients do not receive a psychosocial assessment following self-harm from the perspective of patients and carers. Methods: Between March and November 2019, we recruited 88 patients and 14 carers aged ⩾18 years from 16 mental health trusts and community organisations in the United Kingdom, via social media, to a co-designed qualitative survey. Thematic analyses were used to interpret the data. Results: Patients' reasons for refusing an assessment included long waiting times, previous problematic interactions with staff and feeling unsafe when in the emergency department. Two people refused an assessment because they wanted to harm themselves again. Participants reported organisational reasons for non-assessment, including clinicians not offering assessments and exclusion due to alcohol intoxication. Other patients felt they did not reach clinically determined thresholds because of misconceptions over perceived heightened fatality risk with certain self-harm methods (e.g. self-poisoning vs self-cutting). Conclusion: Our results provide important insights into some of the reasons why some people may not receive a psychosocial assessment following self-harm. Parallel assessments, compassionate care and specialist alcohol services in acute hospitals may help reduce the number of people who leave before an assessment. Education may help address erroneous beliefs that self-injury and self-harm repetition are not associated with greatly raised suicide risk.